The complexity of needs and roles of family members during breast cancer rehabilitation: a qualitative study - Marlene Malmström; Annette Holst-Hansson; Ulrika Olsson Möller (BMC Cancer)
Abstract Background Family members play a crucial role in supporting women with breast cancer during their recovery. In the complex situation of being an informal caregiver, their own health and ability to support the patient needs to be acknowledged. The aim was to explore the experiences, needs and roles of family members throughout the rehabilitation process of women with breast cancer. Methods A qualitative study was conducted, involving semi-structured individual telephone interviews with 20 purposefully selected family members of women with breast cancer (13 men aged 24–79 years, 7 women aged 19–76 years). Data analysis utilized conventional content analysis and used “casing” as the analysis technique. The study is part of the ReScreen randomized controlled trial and all participants gave informed consent. Results The interviews revealed significant variation among family members, leading to the emergence of different typologies based on their reactions and specific preconditions. These typologies included: 1) The case of the assertive and confident team leader, 2) The case of the frustrated but persistent guardian, 3) The case of the reassured bystander, and 4) The case of the neglected outsider. While not mutually exclusive, the cases demonstrated clear similarities and differences in whether individuals felt secure or insecure in the rehabilitation process and their level of involvement in this process. Some described feelings of being involved and active in the process while others experienced not being involved and described feelings of abandonment. However, regardless of their role, family members reported that their own health was seldom considered by healthcare professionals. Conclusions This study sheds light on the concept of “we-disease,” where the role of a family member is interrelated with factors such as their health literacy, supporting role, level of involvement, relationship, and identity during the patient's rehabilitation process. This highlights significant divergence in whether family members perceive the rehabilitation process as a collaborative effort or an individual challenge. These perceptions greatly impact their own well-being and ability to support women with breast cancer, underscoring the importance of recognizing family members as informal caregivers and offering tailored support from healthcare professionals when needed. Trial registration ClinicalTrials.gov NCT03434717. Registered February 15, 2018.